Pertanggungjawaban Ahli Waris Notaris sebagai Pejabat Umum atas Akta Notaris yang Menimbulkan Kerugian Para Pihak - Anang Ade Irawan; A. Rachmad Budiono; Herlin Wijayanti (University of Jember, 2018)
This article discusses the provision of Article 65 of Notary Law (UUJN) which contains the unclear time limit of the notary's responsibility in performing his duties as a public official. The article does not provide explicit explanations to the extent to which the notary no longer holds the responsibility after termination or death to the authentic deeds made. The purpose of this study is to know, identify and analyze the form of accountability of notary heirs as general officials on notarial deeds that cause harm to the parties. By using normative research, there are research results among others. First, based on the theory of fautes personalles, the theory which states that losses to third parties are imposed on officials who because of their actions have caused harm. Second, according to the theory of inheritance that becomes the object of the estate is a wealth in the sense of assets and liabilities. Unlawful acts of civil law are per-artificial wrong done by individuals, so it can not be associated with heirs. The government should make a clearer regulation of the deadline of notary responsibility by adding a separate chapter to the UUJN that regulates notary responsibility. Keywords: Responsibility, Notary Public Notary, Public Official, Notary Deed